Az ellátási lánc versenyképességének növelése az értékelemzés (Value Methodology) alkalmazásával - Nádasdi, Ferenc (Jelenkori Társadalmi és Gazdasági Folyamatok, 2010)
Essentially, the "supply chain" may be seen as several processes linked together. Hun-garian and international experience shows that Value Methodology (VM) can be used ef-fectively in the analysis of particular processes (technologies, services, administrative processes, etc.). We have seen that in addition to enhancing the efficiency of certain stages of processes VM can produce excellent results in linking these stages together. Companies often prematurely stop producing marketable but high cost products. However, VM can often make these products profitable. Relying on the results of several previously success-ful projects we will present several alternative solutions. We did not intend to present en-tire projects but we wished to call attention mostly to some methodological solutions.